Deletion of Epstein-Barr virus latent membrane protein 1 gene in Japanese and Brazilian gastric carcinomas, metastatic lesions, and reactive lymphocytes - Hayashi, Kazuhiko; Chen, Wen-Gang; Chen, Yuan-Yuan; Murakami, Ichiro; Chen, Hong-Li; Ohara, Nobuya; Nose, Soichiro; Hamaya, Kazuo; Matsui, Satoshi; Bacchi, Maura M.; Bacchi, Carlos E.; Chang, Karen L.; et al. (My University, 1998)
A 30-bp deletion in the Epstein-Barr virus (EBV) latent membrane protein 1 (LMP1) gene has been reported in nasopharyngeal carcinoma and EBV- associated malignant lymphomas. Information on this deletion in EBV- associated gastric carcinoma (EBVaGC) is limited. The association of gastric carcinoma (GC) with EBV was examined by EBV-encoded RNA (EBER) in situ hybridization in 510 patients from Japan and 80 patients from Brazil. We studied the prevalence of 30-bp LMP1 gene deletion in EBVaGC in Japan (29 cases) and Brazil (four cases) in comparison with the corresponding EBER1- positive metastatic lesions in lymph nodes (10 cases) and EBV-infected reactive lymphocytes from dissected nonmetastatic lymph nodes (22 cases), microdissected non-neoplastic gastric mucosa of EBVaGC (five cases), and EBV- nonassociated GC (25 cases). We studied the status of the LMP1 gene by Southern blot hybridization of polymerase chain reaction products obtained after amplification with primers flanking the site of the deletion. We also performed EBV typing and LMP1 protein immunohistochemistry. EBV DNA was amplified by polymerase chain reaction in 30 of 33 EBVaGC cases, 8 of 10 metastatic carcinomas, 14 non-neoplastic tissues from 27 EBVaGC cases, and 12 of 25 non-EBV-associated GC cases with EBER1-positive lymphocytes. The 30-bp LMP1 gene deletion was observed in 23 of 26 (88.5%) cases of EBVaGC from Japan and two of four (50%) cases of Brazilian EBVaGC as compared with EBER1- positive reactive lymphocytes from 11 of 14 (78.6%) EBVaGC cases and 9 of 12 (75%) cases of non-EBV-associated GC. The variant type (the 30-bp deletion variant or nondeleted wild type) of LMP1 gene was the same among reactive lymphocytes, primary and secondary lesions of EBVaGC in all cases for which all three tissue types were studied (six of six). There was no correlation between the presence of the 30-bp deletion with depth of cancer invasion or presence of metastasis. Type A was detected in all available EBV-positive cases. The similar high incidence of 30-bp deletion in LMP1 gene in both carcinoma cells and reactive lymphocytes in EBVaGC cases suggests that this deletion may not be relevant to the pathogenesis of EBVaGC.